Analisis Pengaruh Kualitas Pelayanan dan Harga terhadap Kepuasan Konsumen Restoran The Socialite di Kota Surabaya - Nurul Mita Salsa Kirani; Atty Erdiana (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This research aims to analyze the influence of service quality and price on consumer satisfaction at The Socialite Surabaya Restaurant. Service quality and price are the main factors influencing consumer decisions and their loyalty. The research approach uses quantitative methods by collecting data through questionnaires distributed to 97 respondents, selected using purposive sampling techniques. Data analysis was carried out using multiple linear regression to test the influence of the independent variables (service quality and price) on the dependent variable (consumer satisfaction). The research results show that service quality and price have a significant effect on consumer satisfaction. Of these two variables, the price variable has a more dominant influence than service quality. This shows that consumers consider the suitability of price to product quality and price competitiveness more in assessing their satisfaction. Recommendations are given to restaurant managers to maintain competitive price advantages while still paying attention to service quality in order to maintain consumer loyalty.